Toughening epoxy resins by modification with in situ polymerized acrylate copolymer composed of butyl acrylate and glycidyl methacrylate. (March 2015) - Wang, Tao; Wang, Jun; Chen, Wei; Duan, Huajun; Xiao, Hongbo; Wang, Junpeng; Yang, Jingjun
Poly(butyl acrylate–glycidyl methacrylate) (PBG) was prepared by in situ polymerization of butyl acrylate (BA) and glycidyl methacrylate (GMA) and further used as a modifier to improve the comprehensive properties of the epoxy resin curing system. The modified resin system was based on diglycidyl ether of bisphenol, methyl tetrahydrophthalic anhydride, and tris(dimethylaminomethyl)phenol. The influence of copolymer composition on the mechanical properties, thermal performance, and phase behavior of the system was carefully examined. Results showed that the addition of PBG greatly improved the impact strength of the modified epoxy resin. When 15 wt% of the BA/GMA with a weight ratio composition of 7.5/7.5 was added to the epoxy, high-performance-modified epoxy resin was obtained.